Serum levels of chemokines CCL4 and CCL5 in cirrhotic patients indicate the presence of hepatocellular carcinoma - Sadeghi, Mahmoud; Lahdou, Imad; Oweira, Hani; Daniel, Volker; Terness, Peter; Schmidt, Jan; Weiss, Karl Heinz; Longerich, Thomas; Schemmer, Peter; Opelz, Gerhard; Mehrabi, Arianeb (British journal of cancer, 2015)
Most hepatocellular carcinomas (HCCs) are diagnosed at an advanced stage. The prognostic value of serum tumour markers alpha-fetoprotein (AFP) and des-gamma-carboxy prothrombin (DCP) is limited. The aim of our study is to evaluate the diagnostic value of serum growth factors, apoptotic and inflammatory mediators of cirrhotic patients with and without HCC.
Gesehen am 09.07.2020